Socio-Economic Contributions of Edible Wild Plants to the Livelihood of Forest Dwellers in Akure and Idanre Forest Reserves in Ondo State, Nigeria - Olubanji Isiah, Falade; Omomoh , Eromosele Bernard; Akinwonmi , Folasade Caroline; Falade , Abimbola Bridget; Ponnekanti, Sandeep (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study determines socio-economic contributions of edible wild plants to the livelihood of forest dwellers in Akure and Idanre forest reserves in Ondo State, Nigeria. To achieve this, multistage sampling technique was employed for the study. The first stage involves a purposive selection of three large communities from each forest reserve. The second stage involves a random selection of 20 household respondents each from the selected communities. Thus, a total of 120 household respondents were interviewed for the study, using a well structured interview schedule. The results established that almost all the forest dwellers collected and used edible wild plants for food security in the study area. Besides consumption, some were sold to generate income to sustaining their lives. The findings revealed that the respondents selling edible wild plants realized bellow N 25,000:00 per month as gross monthly income from its sales in the study area. Yet it had a significant impact on the income earnings and livelihoods of forest dwellers. The edible wild plants products were majorly categorized as: fruits, leafy vegetables and seeds. Chi-square test confirmed that age of respondents has positive significant association with the uses of edible wild plants, while there was no significant association between gender, religion, educational level and economic status of respondents and uses of edible wild plants in the study area. Cultivation and domestication of these precious edible wild plant species are therefore recommended in order to reduce the pressure placed on the forest, and thus sustain the indigenous knowledge and conservation to continually improve livelihoods in the study area.